Pembuatan Aplikasi Manajemen Karyawan Berbasis Website untuk Pengelolaan Tenaga Kerja yang Efisien di PT Lestari Berkat Sejahtera - Adia Lestari; Khusnul Khotimah; Muhammad Taufiq Sumadi; Arbansyah Arbansyah (JPMNT JURNAL PENGABDIAN MASYARAKAT NIAN TANA, 2024)
Technological developments from time to time continue to develop in a more sophisticated direction. Ease of accessing the internet and inclusive digital solutions are one of the drivers of accelerating digital transformation among society. Digital solutions in the form of applications have become one of the primary tools needed in the world of work and business. One example of the latest information system developments is in the world of mining in terms of workforce management. One of the companies that requires a workforce management information system is PT Lestari Berkat Sejahtera, because this company still uses a manual workforce management system. The author has a solution, namely by creating an employee data management application. The aim of making this application is to provide easy access for HRD staff, admins and employees to view information and manage existing human resource data.